Chemokine-Like Receptor 1 mRNA Weakly Correlates with Non-Alcoholic Steatohepatitis Score in Male but Not Female Individuals - Neumann, Maximilian (Int J Mol Sci, 2016)
The chemokine-like receptor 1 (CMKLR1) ligands resolvin E1 and chemerin are known to modulate inflammatory response. The progression of non-alcoholic fatty liver disease (NAFLD) to non-alcoholic steatohepatitis (NASH) is associated with inflammation. Here it was analyzed whether hepatic CMKLR1 expression is related to histological features of NASH. Therefore, CMKLR1 mRNA was quantified in liver tissue of 33 patients without NAFLD, 47 patients with borderline NASH and 38 patients with NASH. Hepatic CMKLR1 mRNA was not associated with gender and body mass index (BMI) in the controls and the whole study group. CMKLR1 expression was similar in controls and in patients with borderline NASH and NASH. In male patients weak positive correlations with inflammation, fibrosis and NASH score were identified. In females CMKLR1 was not associated with features of NAFLD. Liver CMKLR1 mRNA tended to be higher in type 2 diabetes patients of both genders and in hypercholesterolemic women. In summary, this study shows that hepatic CMKLR1 mRNA is weakly associated with features of NASH in male patients only.